Identification of Subgingival Periodontal Pathogens and Association with the Severity of Periodontitis in Patients with Chronic Kidney Diseases: A Cross-Sectional Study. (2nd April 2015) - Ismail, Fidan Bahtiar; Ismail, Gener; Dumitriu, Anca Silvia; Baston, Catalin; Berbecar, Vlad; Jurubita, Roxana; Andronesi, Andreea; Dumitriu, Horia Traian; Sinescu, Ioanel
Abstract : Background . The aim of our study was to assess the subgingival profile of 9 periodontal pathogens, by means of real-time PCR, in a group of predialysis chronic kidney disease patients with and without periodontal disease and to identify the risk factors associated with periodontal disease in these patients. Material and Methods . This is a single centre cross-sectional cohort study performed on 70 CKD patients. Patients received a full-mouth periodontal examination and the following parameters were assessed: periodontal pocket depth (PPD), clinical attachment level, bleeding on probing, and plaque index; subgingival biofilm samples were collected from the deepest periodontal pocket of each quadrant and were pooled in one transporting unit. Clinical data were drawn from the medical file of the patients. Results . T. denticola (P = 0.001 ), T. forsythia (P < 0.001 ), and P. micros (P = 0.003 ) are significantly associated with periodontal disease in CKD subjects but in a multivariate model only age and T. forsythia remain independent risk factors for periodontal disease in patients with CKD. Conclusions . In our cohort, age and T. forsythia are independently associated with periodontitis in CKD patients. Within the limits of this study, CKD was not significantly associated with a particular subgingival periodontal pathogens profile in periodontitis patients.